High lithium anodic performance of N-doped porous biocarbon-integrated indium sulfide thin nanosheets. (30th March 2017) - Selvamani, V.; Suryanarayanan, V.; Velayutham, D.; Gopukumar, S.
Abstract : Mesoporous indium(iii )sulfide grafts with N-doped porous biocarbon via cost effective wet ball milling, and exhibits a stable capacity of around 407 and 241 mA h g −1 (at 4.0 and 10.0 A g −1 ), making it a promising alternative anode material for lithium ion batteries. Abstract : A mesoporous 3D marigold flower-like indium sulfide (In2 S3 ) microstructure grafted with nitrogen-doped porous carbon nanosheets was synthesised from fish scale biowaste using a simple, scalable, and cost-effective method. The as-obtained composite exhibited a larger surface area (307 m 2 g −1 ) than pristine InS (57 m 2 g −1 ). As the anode in a lithium ion battery, the synthesised composite and pristine materials retained capacities of about 751 and 397 mA h g −1, respectively, after 100 cycles at a current density of 500 mA g −1 . Furthermore, the composite material delivered capacities in the range 1260–297 mA h g −1 when the current density was varied from 0.025 to 10.0 A g −1 . The impressive electrochemical performance of the composite material is associated with the synergetic effect of porous carbon nanosheets in alleviating volume expansion and enhancing reversibility, allowing practical application in lithium ion batteries.